The Image and Likeness of God: Sloterdijk and Irigaray on Selfhood - Venema, Henry Isaac (Ruch Filozoficzny, 2020)
The Cartesian ghosts of modernism are incapable of understanding selfhood. By taking the individual as the ontological foundation for philosophical inquiry, selfhood is abstracted from the fullness of flesh and blood reality and fails to see selfhood as a plurality of interconnections with others that are essential to any attempt at self-understanding. As Paul Ricoeur points out, the self is discipled into selfhood by way of others who are there prior to any notion we may have about our own identity. We pass through a hermeneutical “detour” by way of the other to come back to self. Here we discover what we take as self is in fact given to us by persons, texts and our historical situation. Selfhood is a self in relation with others, and therefore self-knowledge must consider our relational openness to otherness as foundational for who? what? where? and why? we are constituted in this way. It is this relation, or relational space between self and other that I want to explore in this paper.